The Agreement Level of Colorimetric Indicator Paper and pH Meter Examination Compared to Urine Analyzer in Measuring Exudative Pleural Effusion Fluid pH - Muttaqin Huda; Yusup Subagio Sutanto; Jatu Aphridasari (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2026)
Background: Pleural effusion is an abnormal accumulation of fluid in the pleural space, commonly associated with pulmonary infections and malignancies. Measurement of pleural fluid pH is necessary for diagnosis, therapeutic decision-making, and prognostic evaluation. Multiple methods are used, including pH meters, indicator papers, and urine analyzers, but their concordance has not been widely studied in Indonesia. This study aimed to assess the agreement of pleural fluid pH results measured using pH meters, indicator papers, and urine analyzers to support the appropriate selection of diagnostic methods. Methods: This observational analytic study with a cross-sectional design was conducted at dr. Moewardi General Hospital, Surakarta, from February to June 2025. The sample consisted of 55 patients with exudative pleural effusion who met the inclusion criteria. Pleural fluid pH was measured using three methods: colorimetric indicator paper, a pH meter, and a urine analyzer. Data were analyzed using the Kappa coefficient and the Intraclass Correlation Coefficient (ICC) to assess the agreement between methods. Results: The mean pH values of pleural fluid measured by the urine analyzer, pH meter, and colorimetric indicator paper were 8.18±0.47, 8.13±0.46, and 8.15±0.59, respectively. Agreement analysis showed a very strong and statistically significant correlation between the pH meter and urine analyzer (ICC=0.948; P<0.001), between the pH strip and urine analyzer (ICC=0.855; P<0.001), and between the pH meter and pH strip (ICC=0.916; P<0.001). A significant positive correlation was also observed between glucose levels and pH measured by both the urine analyzer and the pH meter. Conclusion: There is good agreement among pH measurements obtained using colorimetric indicator paper, urine analyzer, and pH meter in exudative pleural effusion fluid.